2014
DOI: 10.1016/j.pain.2014.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous electrical nerve stimulation for the control of pain during rehabilitation after total knee arthroplasty: A randomized, blinded, placebo-controlled trial

Abstract: This study evaluated the efficacy of TENS in reducing pain and hyperalgesia and increasing function following total knee arthroplasty (TKA). We hypothesized participants using TENS during rehabilitation exercises would: 1) report significantly lower pain during range-of-motion (ROM) and fast walking but not at rest; 2) have less hyperalgesia; and, 3) have better function than participants receiving Placebo-TENS or Standard Care. We also hypothesized that change in ROM pain would differ based on psychological c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
98
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(104 citation statements)
references
References 72 publications
4
98
2
Order By: Relevance
“…The primary aim results have been reported elsewhere [44]. Data from the preoperative (baseline) clinic visit only were used for this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary aim results have been reported elsewhere [44]. Data from the preoperative (baseline) clinic visit only were used for this study.…”
Section: Methodsmentioning
confidence: 99%
“…The distance walked was then assessed with a measuring tape. Further details on this and the ROM procedures can be found in a prior publication [44]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination therapy also reduces the required dose of individual medication which further lowers the incidence of medication adverse events. Other alternative modalities such as cryotherapy, through the application of cool water to the surgical site or transcutaneous electrical nerve stimulation (TENS) are also taken into consideration, as studies have shown to reduce the acute pain after surgery [42,43].…”
Section: Pain Reliefmentioning
confidence: 99%
“…Transcutaneous electrical nerve stimulation (TENS) for control of postoperative pain has been used after various procedures, including cardiac surgeries [8e12], cholecystectomy [13e15], cesarean section [16,17], liposuction [18], total knee arthroplasty [19], and thoracotomy [20e25]. Treating pain with TENS is based on 2 theories.…”
Section: Introductionmentioning
confidence: 99%